2020
DOI: 10.1093/gbe/evaa150
|View full text |Cite
|
Sign up to set email alerts
|

Population Genomic Analyses of the Sea Urchin Echinometra sp. EZ across an Extreme Environmental Gradient

Abstract: Extreme environmental gradients represent excellent study systems to better understand the variables that mediate patterns of genomic variation between populations. They also allow for more accurate predictions of how future environmental change might affect marine species. The Persian/Arabian Gulf is extreme in both temperature and salinity while the adjacent Gulf of Oman has conditions more typical of tropical oceans. The sea urchin Echinometra sp. EZ inhabits both of these seas and plays a critical role in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 70 publications
(79 reference statements)
4
10
0
Order By: Relevance
“…In the summer‐winter spatial series, the majority of the variation in the data was explained by collection site where PC 1 differentiated the PAG from the GO. This microbial differentiation was congruent with previous analyses on the genetic structure of the host species, which showed two populations, one in the PAG and one in the GO (Ketchum et al, 2020). The Musandam collection site is located within the Strait of Hormuz and is geographically situated at the connection between the two seas.…”
Section: Discussionsupporting
confidence: 92%
“…In the summer‐winter spatial series, the majority of the variation in the data was explained by collection site where PC 1 differentiated the PAG from the GO. This microbial differentiation was congruent with previous analyses on the genetic structure of the host species, which showed two populations, one in the PAG and one in the GO (Ketchum et al, 2020). The Musandam collection site is located within the Strait of Hormuz and is geographically situated at the connection between the two seas.…”
Section: Discussionsupporting
confidence: 92%
“…Genetic drift may also account for the higher degree of genetic differentiation found between TX and the other southwest populations compared with that found between TX and the north populations. Given that the TX population is geographically located in the southwest of the Tarim Basin, the identified population structure might also reflect the different environmental conditions across the Tarim Basin (i.e., temperature and altitude), which may impose different types of selective pressure on Yarkand hares, as observed for other species such as Diptychus maculates [ 24 ] and urchins [ 72 ] according to genome-wide SNP-based analysis. Future studies should include historical demographic events such as range expansions and population bottlenecks in such analyses, which may shape allele frequency patterns between populations, to explore these hypotheses based on genome-wide SNP markers.…”
Section: Discussionmentioning
confidence: 99%
“…Weak genetic discontinuity between the Gulf and the adjacent Sea of Oman has been shown for a coral species Platygyra daedalea (Howells et al, 2016), which spawn mainly from February to May (Bauman et al, 2011), and a sea urchin Echinometra sp. (Ketchum et al, 2020), whose PLD within the genus vary from 18 to 30 days (McClanahan & Muthiga, 2007). On the other hand, population genetics studies showed that for reef fish species, such as C. hemistiktos (Priest et al, 2016) and P. maculosus (Torquato et al, 2019), the Gulf and the Sea of Oman represent a single phylogeographic province.…”
Section: Discussionmentioning
confidence: 99%